Hypertext preprocessor framework in the development of web applications - Saroni, M I N; Mulyanti, B (IOP conference series. Materials Science and Engineering, 2020)
This writing paper aims to determine the Hypertext Preprocessor (PHP) framework that is widely used and analyze the benefits of the framework in making a web application. A review systematically through a review article about a PHP framework. Article search is accessed from an internet database search. articles are taken from 2014 to 2019. The PHP framework can simplify the process of developing web applications because the concept has already been determined. Whereas if you use regular PHP, a programmer makes coding, folder structure or configuration is made as he wishes. Usually, the PHP framework uses the concept of Model-View-Controller (MVC), its function model is for database queries, its View function is for displaying HTML (Hypertext Markup Language), the controller functions for calculations or logic. The result is that PHP Laravel and CodeIgniter frameworks are the most widely used in building a web application. PHP Framework makes the development of applications web becomes much faster and more stable. The selection of a PHP framework that is appropriate for the project of making the application web also can affect the outcome performance was obtained after the application of the web was completed.